Tantangan dan Permasalahan Penegakan Hukum Tindak Pidana Korupsi di Indonesia - Wiranti, Yenni; Arifin, Ridwan (Kosmik Hukum, 2020)
Corruption is an extraordinary crime. It grows in the human body because man's eternal nature is greed. Corruption is an act committed with the intention of obtaining several benefits that is contrary to official duties and other truths. The Corruption Law is regulated in Law Number 31 Year 1999. It is understandable if corruption is so difficult to eradicate, partly because the approach used is still partial, whereas the handling needed is a multidimensional approach. The wide enough social and power gap in the structure of society also influences the opening of opportunities for corruption, which in turn contributes greatly to the culture of corruption. Keywords: Corruption, Eradication, Causes of Corruption, Law Enforcement